Manfaat Infused Water dalam Mendukung Sistem Imun - A. Taufiq (Mutiara Pendidikan dan Olahraga, 2025)
Infused water is a functional beverage made by soaking slices of fruits, vegetables, and herbs in mineral water to produce a natural flavor and enhance nutritional content. In recent years, infused water has become part of a healthy lifestyle trend due to its claimed benefits, including detoxification, improved hydration, and immune system enhancement. This article aims to review the latest scientific literature on the potential benefits of infused water on immune function, particularly in the context of regular consumption of natural ingredients such as lemon, ginger, strawberries, and herbs that are rich in vitamin C, antioxidants, and flavonoids. The review was conducted by searching scientific databases such as PubMed, Google Scholar, and ScienceDirect, using inclusion criteria that covered publications from 2020 to 2024. The findings indicate that infused water containing vitamin C, gingerol, and polyphenolic compounds can help improve immune function by reducing oxidative stress, suppressing inflammatory responses, and stimulating immune cell activity such as lymphocytes and macrophages. Furthermore, optimal hydration from infused water supports various physiological processes of the immune system. In conclusion, infused water holds potential as a simple, natural, and cost-effective strategy to support immune health. However, further research is needed to evaluate its efficacy, optimal formulations, and dosage for maximum benefit.